Bridging the marrow: a co-culture-platform of leukemia cells and MS5-derived stromal cells or adipocytes - Julia Zinngrebe; Elena Dorothea Brenner; Ferdinand Schlichtig; Ulrich Stifel; Daniel Tews; Jana Falk; Dominik Schlotter; Rahel Fitzel; Lüder-Hinrich Meyer; Klaus-Michael Debatin; Pamela Fischer-Posovszky (Cell Death Discovery)
Abstract In the context of acute lymphoblastic leukemia (ALL), the bone marrow microenvironment (BMM) plays a crucial role in providing pro-survival signals, as evident from the rapid spontaneous cell death observed in ex-vivo cultures of primary ALL cells. Among the diverse cell types within the BMM, bone marrow adipocytes (BMAd) exhibit significant plasticity and can constitute a substantial part of the BMM, especially during ALL therapy. However, conflicting data on the interaction between ALL cells and adipocytes have been reported, potentially arising from variations in culture systems and conditions. Our study aimed to establish a chemically defined co-culture system of leukemia cells combined with either bone marrow (BM)-derived stromal cells or adipocytes. Established B-precursor ALL cell lines, patient-derived ALL xenografts (PDX), and murine BM-derived MS5 stromal cells and adipocytes were used as model systems. Fetal calf serum and factors included in the adipogenic media significantly impacted leukemia cell viability and proliferation. Thus, we implemented a washing procedure and suitable, chemically defined media conditions into our co-culture platform. In general, ALL cell lines survived and proliferated on both stromal cells and adipocytes, whereas PDX cells exhibited a pronounced survival advantage on stromal cells compared to adipocytes. Intriguingly, the presence of adipocytes sensitized cell lines and PDX cells to chemotherapy with anthracyclines or dexamethasone when compared to co-cultures with stromal cells. Thus, utilizing the well-established MS5 cell line together with the optimized culture conditions in our co-culture system provides a reliable, open-access platform for investigating intricate interactions between bone marrow stromal cells, adipocytes, and leukemia cells.